A Review on Preclinical Models of Ischemic Stroke: Insights Into the Pathomechanisms and New Treatment Strategies - Singh, Aditya A.; Kharwar, Akash; Dandekar, Manoj P. (Current Neuropharmacology, 2022)
Background: Stroke is a serious neurovascular problem and the leading cause of disability and death worldwide. The disrupted demand to supply ratio of blood and glucose during cerebral ischemia develops hypoxic shock, and subsequently necrotic neuronal death in the affected regions. Multiple causal factors like age, sex, race, genetics, diet, and lifestyle play an important role in the occurrence as well as progression of post-stroke deleterious events. These biological and environmental factors may be contributed to vasculature variable architecture and abnormal neuronal activity. Since recombinant tissue plasminogen activator is the only clinically effective clot bursting drug, there is a huge unmet medical need for newer therapies for the treatment of stroke. Innumerous therapeutic interventions have shown promise in the experimental models of stroke but failed to translate it into clinical counterparts. Methods: Original publications regarding pathophysiology, preclinical experimental models, new targets and therapies targeting ischemic stroke have been reviewed since the 1970s. Results: We highlighted the critical underlying pathophysiological mechanisms of cerebral stroke and preclinical stroke models. We discuss the strengths and caveats of widely used ischemic stroke models, and commented on the potential translational problems. We also describe the new emerging treatment strategies, including stem cell therapy, neurotrophic factors and gut microbiome-based therapy for the management of post-stroke consequences. Conclusion: There are still many inter-linked pathophysiological alterations with regards to stroke, animal models need not necessarily mimic the same conditions of stroke pathology and newer targets and therapies are the need of the hour in stroke research.
Keywords: pathophysiology